Intergroup Dialogue: A Review of Recent Empirical Research and Its Implications for Research and Practice. (October 2019) - Frantell, Keri A.; Miles, Joseph R.; Ruwe, Anne M.
Intergroup dialogue (IGD) is a small group intervention that allows for sustained communication between people across social identity groups. It aims to foster intergroup relationships, develop critical consciousness, and increase capacities for promoting social justice. A decade after Dessel and Rogge published their review of the empirical research on IGD from 1997 to 2006, we reviewed the empirical IGD research from 2006 to 2017. We explore research that has examined IGD outcomes, processes, and facilitation, seeking to understand the current state of the research and practice of IGD. We discuss advances and new approaches to IGD, assess growth since Dessel and Rogge's review, and discuss future directions. We provide five key recommendations for future research on IGD, and five key recommendations for future practice of IGD.